(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The essay examines the bills on medically assisted death currently under debate in Italy, the United Kingdom, and France, comparing how the three legal systems seek to regulate assistance in dying for patients who wish to end the suffering caused by illness with the cooperation of others. The comparative analysis considers the structure of these legislative proposals, with particular attention to the place accorded to the patient and their needs, as well as to the effectiveness of the safeguards intended to protect the requester’s self-determination in each national context.